High‐Performance 2D p‐Type Transistors Based on GaSe Layers: An Ab Initio Study. (11th January 2017) - Kuc, Agnieszka; Cusati, Teresa; Dib, Elias; Oliveira, Augusto F.; Fortunelli, Alessandro; Iannaccone, Giuseppe; Heine, Thomas; Fiori, Gianluca
Abstract : Ultrascaled GaSe field effect transistors are investigated through ab initio calculations . GaSe monolayers, 3 nm long, exhibit excellent performance with reduced short‐channel effects and considerably high ON‐current. Such device characteristics are due to the valence band edge shape, which leads to very heavy holes in the transport direction and eventually suppresses intraband tunneling, detrimental for correct operation in the OFF state.